Money and Irish Catholicism: an intimate history, 1850-1921 - Roddy, Sarah (Cambridge University Press, 2025)
In the decades after the Great Famine, from about 1850, the Irish Catholic Church underwent a 'devotional revolution' and grew wealthy on a 'voluntary' system of payments from ordinary lay people. This study explores the lives of the people who gave the money. Focusing on both routine payments made to support clerical incomes and donations towards building the vast Catholic infrastructure that emerged in the period, Money and Irish Catholicism offers an intimate insight into the motivations, experiences, and emotions of ordinary people. In so doing, it offers a new perspective on the history of Irish Catholicism, focused less on the top-down exploits of bishops, priests, and nuns, and more on the bottom-up contributions of everyday Catholics. Sarah Roddy also demonstrates the extent to which the creation of the modern Irish Catholic Church was a transnational process, in which the diaspora, especially in the United States, played a vital role